Criminalising Migrant Smuggling in Canada - Jimenez, Estibaliz (Criminologie)

(untitled) (Les Presses de l’Université de Montréal, 2022)
Irregular migration is seen by the international community as a security issue and the criminalization of immigration has become a tool for migration control and border security. In recent years, Canada has taken a punitive approach toward irregular immigration and increasingly relies on criminalization to deal with it, adopting more severe penalties, including life imprisonment. Paradoxically, despite tougher legislation that includes mandatory minimum sentences and increased maximum sentences, Canadian courts tend to give migrant smugglers short-term prison sentences or conditional sentences that are served in the community. This paper presents the results of a legal analysis relating to the smuggling of migrants in Canada. The results show that sentences given by the courts are not proportional to the political discourse and alarmist messages in the media regarding the threat posed by the smuggling of migrants.